The effect of climate change on rainfall pattern and deficit of water in tea plantation - Salwa Lubnan Dalimoenthe; Y Apriana; T June (Jurnal Penelitian Teh dan Kina, 2016)
Climate change has been influencing rainfall pattern so that it would be necessary to see the impact of that changed on tea plantation. The experimental area coverage lowland (600 m asl), midland (800-1000m asl) and highland (>1.000 m asl) tea plantation and each altituted represented by three tea estate in West Java. The rainfall data collected since 2005 up to 2014 from each estate and water deficit has been count through the method develop by Wijaya (1996). The results showed that the rainfall pattern has been changed by La-Nina and El-Nino during 2005-2014 in tea estate either in lowland, midland or highland in the last decade. The climate change causedÂ  rainfall decreasing and increasing on dry month (the rainfall < 100 mm). Eventhough on 2009 there is an significantly increasing of the rainfall but after 2009 until 2014, the rainfall tend to decrease. After El-Nino on late 2009 and early 2010, lowland tea estate on Subang Regency facing water deficit until 5 months with R (defisit water index) far below 1 even there is no El Nino. The tea plantation at midland area (Cianjur Regency) facing 5 months water deficit per year, but the R index close to 1. While in highland tea plantation (Bandung Regency), the water deficit only happend on certain month on certain year although there is a month with zero rainfall. Water deficit could be happend because of runoff on soil surface stimulate by low ability of soil to keep the water.